Studying mind and brain with fMRI - Berman, Marc G. (Oxford University Press, 2006)
The explosion in publications using functional magnetic resonance imaging (fMRI) warrants an examination of how the technique is being used to study processes of mind and brain. Here, we propose a classification of fMRI studies that reveals how this technique is being used in the service of understanding psychological and neural processes and the relationship between the two.